2003
DOI: 10.1046/j.1468-3148.2003.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Women be Healthy: Evaluation of a Women's Health Curriculum for Women with Intellectual Disabilities

Abstract: Background  Insufficient attention has been paid towards treating the unique health needs of women with intellectual disabilities. This paper describes an 8‐week curriculum, ‘Women Be Healthy’, developed for women with intellectual disabilities to help them become more equal partners in their health care. The curriculum includes psycho‐education, coping skills training, exposure to the medical setting and assertiveness training. Materials and methods  Twenty‐two women completed assessments of health knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 17 publications
2
76
0
1
Order By: Relevance
“…Progress has been made within the past decades in exploring women's health education resources and programs for this population (Health Resource Center for Women With Disabilities, 2001;Heaton et al, 1994;Lunsky, Straiko, & Armstrong, 2003;Simpson & Lankasky, 2001;Wyoming Institute for Disabilities, 2004), but questions remain regarding how best to support women in community programs and, in particular, what roles they have in addressing or preventing their own health issues. More research is needed on creating health-promotion options for these women and should explore differences across age, race, ethnicity, and class.…”
Section: Resultsmentioning
confidence: 99%
“…Progress has been made within the past decades in exploring women's health education resources and programs for this population (Health Resource Center for Women With Disabilities, 2001;Heaton et al, 1994;Lunsky, Straiko, & Armstrong, 2003;Simpson & Lankasky, 2001;Wyoming Institute for Disabilities, 2004), but questions remain regarding how best to support women in community programs and, in particular, what roles they have in addressing or preventing their own health issues. More research is needed on creating health-promotion options for these women and should explore differences across age, race, ethnicity, and class.…”
Section: Resultsmentioning
confidence: 99%
“…The greater likelihood of ED visits among women with IDD could be associated with poorly communicated or inadequate postpartum discharge instructions. Health literacy tends to be low among people with IDD and verbal or text-based hospital discharge instructions may not be readily accessible to these women 34. Conceivably, medical concerns and/or postpartum care instructions were not observed, communicated or adequately noted, increasing the likelihood of foregone medical care and treatment-seeking in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to suspect that the rates of postpartum psychiatric emergencies among women with IDD reported here are an underestimate. Women with IDD may have difficulty communicating their symptoms,34 particularly during a pysychiatric emergency. Additionally, clinicians often feel unable to adequately care for people with IDD, and are likely less able to recognise psychiatric symptoms and behaviours in ED settings.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported here are part of a larger study that tested and reflned Women Be Healthy (Lunsky, Straiko, & Armstrong, 2002), a psycho-educational program designed to increase cervical and breast cancer screenings for women with intellectual disability. A randomized control trial of Women Be Healthy was conducted across 21 sites in one southeastern state in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…Female caregivers were eligible to participate if they lived with a woman enrolled in the larger study testing Women Be Healthy (Lunsky et al, 2002). From a sample of 179 women with intellectual disability enrolled in the larger study, 87 reported they lived at home with at least one female caregiver.…”
Section: Sample Recruitment and Selectionmentioning
confidence: 99%